Pengaruh Social Media Marketing Activities, Influencer Marketing, dan Brand Image Terhadap Brand Loyalty di Instagram @elzattahijab - Akbar Dwi Nurrasyid; Nurul Azizah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the impact of social media marketing activities (SMMA), influencer marketing, and the influence of brand image on brand loyalty for Elzatta Hijab's Muslim fashion products. Using a systematic quantitative approach, data was collected through closed-ended questionnaires from 204 followers of Elzatta Hijab's Instagram account who met specific criteria. The data analysis method employed in this study was multiple linear regression, with the analysis conducted using SPSS 26 for Mac. The results show that all three variables have a significant impact on brand loyalty, both simultaneously and partially. These findings emphasize the importance of digital marketing strategies in building and maintaining brand loyalty, with influencer marketing being the most dominant factor affecting brand loyalty. The study recommends that companies continue to enhance the quality of their social media marketing activities, collaborate with relevant influencers, and maintain a positive brand image to stay competitive in the market.